ncRNAs: an unexplored cellular defense mechanism in leprosy - Santana-da-Silva, Mayara Natália; Sena-dos-Santos, Camille; Cáceres-Durán, Miguel Ángel; Souza, Felipe Gouvea de; Gobbo, Angelica Rita; Pinto, Pablo; Salgado, Claudio Guedes; dos Santos, Sidney Emanuel Batista (Frontiers in Genetics, 2023)
Leprosy is an infectious disease primarily caused by the obligate intracellular parasite Mycobacterium leprae. Although it has been considered eradicated in many countries, leprosy continues to be a health issue in developing nations. Besides the social stigma associated with it, individuals affected by leprosy may experience nerve damage leading to physical disabilities if the disease is not properly treated or early diagnosed. Leprosy is recognized as a complex disease wherein socioenvironmental factors, immune response, and host genetics interact to contribute to its development. Recently, a new field of study called epigenetics has emerged, revealing that the immune response and other mechanisms related to infectious diseases can be influenced by noncoding RNAs. This review aims to summarize the significant advancements concerning noncoding RNAs in leprosy, discussing the key perspectives on this novel approach to comprehending the pathophysiology of the disease and identifying molecular markers. In our view, investigations on non-coding RNAs in leprosy hold promise and warrant increased attention from researches in this field.